2004
DOI: 10.1002/app.13500
|View full text |Cite
|
Sign up to set email alerts
|

Morphology investigation of transcrystallinity at polyamide 66/aramid fiber interface

Abstract: ABSTRACT:The morphology of PA66/Kevlar-129 fiber specimens was investigated by means of polarized optical microscopy and scanning electron microscopy. The results indicated that, at crystallization temperatures ranging from 100 to 220°C, the transcrystallinity (TC) interphase always occurs. Both the TC interphase and spherulite morphology were present under various crystallization conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It was reported that the i PP TCL layer consists of two layers, and the inner layer possesses polymer chains parallel oriented along the fiber direction, and this layer is around 300 nm according to Kitayama et al In the other layer, which was more than 300 nm far away from the fiber surface, cross-hatched structures composed of parent lamellae (similar to the inner layer) and daughter lamellae (the epitaxy angle of daughter lamellae is around 80° with respect to that of parent lamellae), as shown in Figure b,c. Until now, TCL formation has been observed in most of the semicrystalline polymers, such as i PP, PE, PA, PPS, PLLA, polybutene (PBu), and PEEK . The mechanism of TCL formation on the fiber surface is very complicated, and there are several proposals, like a fiber surface’s topography, chemistry, and residual stress during fiber introduction to the matrix .…”
Section: Hsk-like Structures With Commercial Synthetic and Natural Fi...mentioning
confidence: 99%
“…It was reported that the i PP TCL layer consists of two layers, and the inner layer possesses polymer chains parallel oriented along the fiber direction, and this layer is around 300 nm according to Kitayama et al In the other layer, which was more than 300 nm far away from the fiber surface, cross-hatched structures composed of parent lamellae (similar to the inner layer) and daughter lamellae (the epitaxy angle of daughter lamellae is around 80° with respect to that of parent lamellae), as shown in Figure b,c. Until now, TCL formation has been observed in most of the semicrystalline polymers, such as i PP, PE, PA, PPS, PLLA, polybutene (PBu), and PEEK . The mechanism of TCL formation on the fiber surface is very complicated, and there are several proposals, like a fiber surface’s topography, chemistry, and residual stress during fiber introduction to the matrix .…”
Section: Hsk-like Structures With Commercial Synthetic and Natural Fi...mentioning
confidence: 99%
“…Fiber-induced interfacial crystallization is recognized as a promising method to improve polymer/fiber interfacial interactions. ,, It effectively accelerates the nucleation kinetics of the matrix by providing more nucleation sites. A special heterogeneous nucleation morphology, termed the transcrystalline layer (TCL), is produced as a result of the most important kind of interfacial interactions and has been widely reported and under focus recently. , The formation of TCL is associated with an extremely high nucleating ability of the fibers, causing the crystals to grow perpendicular to the fiber axis. Many factors, such as surface chemistry and roughness of the fiber, ,,, molecular weight, chain conformation, and functional groups of the polymer matrix, are believed to affect surface-induced nucleation in composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This peculiar morphology is addressed as transcrystalline layer (TCL), and is typically associated to the high nucleating ability of the embedded fibers' surface. [4][5][6][7][8][9][10][11][12] The formation of TCL is of technological importance, because it can significantly influence the mechanical properties of the product. [13][14][15][16][17][18][19] In fact, TCL presents a higher Young's modulus compared with the bulk materials, despite a lower strain at break.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber composites of semicrystalline polymers are able to develop, under certain conditions, a highly oriented crystalline layer with molecular chain axis parallel to fiber axis at the fiber/matrix interface. This peculiar morphology is addressed as a transcrystalline layer (TCL) and is typically associated with the high nucleating ability of the embedded fibers’ surface. The formation of TCL is of technological importance because it can significantly influence the mechanical properties of the product. In fact, TCL presents a higher Young’s modulus compared with the bulk materials, despite a lower strain at break. , Moreover, the presence of TCL can effectively improve the adhesion between the polymer and fiber, thus increasing the flexural modulus and strength of the composites …”
Section: Introductionmentioning
confidence: 99%